Learning tools of KVK module using augmented reality mobile application for remedial education program (REP) - Ayub, A. A.; Othman, M.; M. Sahar, Nan; M. N. Azni, M. S.; Ilyas, M. A.; Jaafar, M. (2020)
Augmented Reality (AR) is one of the technologies that has increased popularity in industry revolution 4.0 (IR 4.0). This technology is widely used in the education sector that can help the students easily acquire, process, and remember the information. However, due to the lack of introduction to new technology in some education fields, primary students tend to only use conventional learning methods such as books or card games. By looking at this loophole, this project is focusing on the primary students that being called remedial students in Remedial Education Program (REP). We choose the consonant vowel consonant (KVK) module after a deep discussion with the remedial teacher and regional education officer in Batu Pahat. The record shows that remedial students are facing hardship to spell, read, and pronounce the KVK. We have successfully developed the AR application education platform apps by using the Unity Real-Time Development platform (Unity 3D) and Vuforia. Inside this application, there are two menus for learning purposes which are KVK and Suku Kata and one menu for evaluation which is Kuiz. This module has been tested to 25 remedial students and the results show that the evaluation time taken to answer the Kuiz from the apps has been reduced around 10% to 50% compared to the conventional method. We hope that this application can be applied widely for remedial students in elementary school in year one that has a problem in mastering the KVK for REP.